Issues and Challenges in the Development of Electronic Health Records in Malaysia and Vietnam - Nguyen, Q.T. (2008)
This paper discusses some of the current issues and challenges facing governments and healthcare industries in Asia, with regard to the development of their Electronic Health Records systems. Particular emphasis is placed on Malaysia and Vietnam. Whereas Malaysia has already embarked on a strategic and comprehensive programme of development, Vietnam is still seeking the way to best develop its approach to the development of its healthcare policies and to the development of an effective Electronic Health Records system.